Comparative Analysis of Mass Media Coverage of the Fight Against Corruption in Nigeria by the Obasanjo and Buhari Administrations - Okon, Patrick Ene (International Journal of Emerging Trends in Social Sciences, 2018)
Since Nigeria returned to democratic governance in May 1999, the fight against corruption has been a major preoccupation of every administration in the country. This paper comparatively analysed the frequency, prominence and depth of coverage given to this "fight" by the Nigerian media during the administrations of former President Olusegun Obasanjo (1999 – 2007) and incumbent President Muhammadu Buhari (2015 – date). Content analysis was the research instrument used to generate data. For Obasanjo era, 39 issues each of The News and TELL magazines selected through systematic sampling technique from the first three years of the administration were used; while for Buhari era, 26 issues each of two newspapers – the privately-owned Sun, and State Government-owned Nigerian Chronicle – were selected from within the first six months of 2017 based on the composite week sampling technique. Content categories of editorial items on corruption used were bribery, forgery/perjury, fraud, misappropriation and mismanagement, while units of analysis were news, features/opinions/columns, editorials, photographs/cartoons, advertorials, and letters to editor. Attention score was on prominence, depth, frequency, and slant. Theoretical framework anchored on the Agenda-Setting Theory. Research findings from each segment of the study were descriptively discussed and comparatively analysed using frequency count, attention score and percentage mean. It was concluded that the trends in media coverage under the two administrations were similar. Recommendations made included: that the media should be more consistent, persistent and responsible in their coverage of anti-corruption issues; while the government should be more proactive and all-inclusive in the fight against corruption.